2019
DOI: 10.32440/ar.2018.135.03.rev01
|View full text |Cite
|
Sign up to set email alerts
|

Hip fracture: A 21st century socio-sanitary epidemic in the first world

Abstract: El autor/a de este artículo declara no tener ningún tipo de conflicto de intereses respecto a lo expuesto en la presente revisión. a 210

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
2
0
3
Order By: Relevance
“…Efficient early rehabilitation is based on postural recommendations, muscle strengthening, balance aids, gait reeducation, and training in daily life activities, and thus promoting different skills to achieve the best possible functional status. 4 As part of the multidisciplinary team that cares for patients with hip fractures, rehabilitation physicians indicate the type of recovery program, and physical therapists are involved in helping elderly patients to regain mobility and resume early weight-bearing. 47 Postoperative gait analysis also plays an essential role in adapting physiotherapy to the difficulties encountered by the patient, tolerance to pain while walking, and in overcoming the fear of new falls.…”
Section: Postoperative Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient early rehabilitation is based on postural recommendations, muscle strengthening, balance aids, gait reeducation, and training in daily life activities, and thus promoting different skills to achieve the best possible functional status. 4 As part of the multidisciplinary team that cares for patients with hip fractures, rehabilitation physicians indicate the type of recovery program, and physical therapists are involved in helping elderly patients to regain mobility and resume early weight-bearing. 47 Postoperative gait analysis also plays an essential role in adapting physiotherapy to the difficulties encountered by the patient, tolerance to pain while walking, and in overcoming the fear of new falls.…”
Section: Postoperative Recommendationsmentioning
confidence: 99%
“…The main objective of the current review was to shed light on an issue that, although rarely reported, probably happens more often, given the epidemic of hip fractures in the 21st century. 4 Moreover, the authors set out to develop a CPG for optimal management of elderly patients with simultaneous bilateral extracapsular hip fractures, highlighting differential concerns compared with unilateral cases. This review of previously published material was exempt from institutional review board approval.…”
Section: Introductionmentioning
confidence: 99%
“…La frecuencia de las fracturas de cadera se ha ido incrementando en los últimos años debido al aumento de la edad de la población. 1 Estas fracturas conllevan una alta morbimortalidad, provocan grandes limitaciones y dificultades para recuperar la marcha, y pueden llevar a complicaciones graves, como enfermedad tromboembólica venosa, neumonía o úlceras por presión. 2 Es por ello que la intervención quirúrgica precoz y el inicio temprano de la marcha son imprescindibles en la mayoría de estos pacientes.…”
Section: Introductionunclassified
“…Clásicamente se caracterizan por ser fracturas en dos fragmentos con un trazo en la base del cuello femoral, medial a la línea intertrocantérica, por encima del trocánter menor (Figura 1). 1,2 Son poco frecuentes, pues su prevalencia oscila entre el 1,8% y el 7,7%. 3,4 Su tratamiento es complejo, porque su situación intermedia entre las fracturas intracapsulares y extracapsulares provoca una alta inestabilidad biomecánica axial (su trazo, más vertical y lateral que el de las fracturas pertrocantéricas, se ve sometido a mayores fuerzas cizallantes y varizantes) y rotatoria (ya que el fragmento proximal carece de inserciones musculares que lo fijen), lo que conlleva una elevada tasa de complicaciones (hasta del 54%), entre ellas, se destaca el fenómeno de cut-out.…”
Section: Introductionunclassified
“…Dado estos avances en la expectativa de vida reflejados de igual forma en la población de nuestro país en vías de desarrollo, es menester proporcionar la atención integral de salud en base al perfil epidemiológico de éste grupo etareo donde se recalca: el número de adultos mayores con osteoporosis, caídas que trae como consecuencia las fracturas de cadera (Marco, Galán Olleros, Mora Fernández, & Mora-Fernández, 2019).…”
Section: Introductionunclassified